Extreme thrombocytosis as a rare initial manifestation of chronic myeloid leukemia: A case report - Brahmantya, Herwindo; Insanfadhil, Muhammad (PT. DEKA RESEARCH INSTITUTE, 2025)
BACKGROUND: Severe thrombocytosis is a rare presentation of chronic myeloid leukemia (CML), but can be associated with rapid advancement of the disease and severe consequences. The aim of this case report is to describe the management of CML with severe thrombocytosis simulating essential thrombocythemia (ET). CASE: A 29-year-old male presented to emergency department with the symptoms of pain and swelling in left lower limb for four days. Swelling began in thigh and gradually spread to lower leg and was accompanied by pain on movement. Patient was diagnosed with CML in 2019 and on Imatinib 400 mg/day since then. Physical exam showed anemic conjunctiva, splenomegaly (Schuffner 1/8), and palpable mass of left gastrocnemius muscle. MRI revealed an intramuscular cystic mass suggestive of a lymphangioma. Laboratory results presented with severe anemia, leukocytosis, and spectacular thrombocytosis (6,143,000/µL). Bone marrow aspiration revealed elevated granulopoiesis and megakaryopoiesis, 10% myeloblasts, 5:1 myeloid-to-erythroid ratio, and positive platelet aggregation. Chronic-phase CML with transformation imitating ET was the diagnosis rendered. Treatment was with hydroxyurea, nilotinib, aspirin, intravenous fluids, and thrombocytapheresis. Two days after thrombocytapheresis, the patient complained of significant clinical improvement and was able to walk independently with minimal residual pain. CONCLUSION: CML with massive thrombocytosis is noteworthy to present specifically as it may mimic ET and carry a risk of thrombotic complications. Therapy by multimodal approach using TKI, cytoreduction, and thrombocytapheresis may be highly effective.